Effect of Polyethylene Glycol Additive on the Structure and Performance of Fabric-Reinforced Thin Film Composite - Xiao Wang; Yuntao Zhao; Xueyou Wen (Molecules, 2023)
Fabric-reinforced thin film composite (TFC) membranes exhibit outstanding mechanical durability over free-standing membranes for commercial applications. In this study, polyethylene glycol (PEG) was incorporated to modify the polysulfone (PSU) supported fabric-reinforced TFC membrane for forward osmosis (FO). The effects of PEG content and molecular weight on the structure, material property and FO performance of the membrane were investigated comprehensively, and the corresponding mechanisms were revealed. The membrane prepared by using 400 g/mol PEG exhibited better FO performances than those of membranes with 1000 and 2000 g/mol PEG, and 20 wt.% was demonstrated to be the optimal PEG content in the casting solution. The permselectivity of the membrane was further improved by reducing the PSU concentration. The optimal TFC-FO membrane had a water flux <semantics>(Jw)</semantics> of 25.0 LMH using deionized (DI) water feed and 1 M NaCl draw solution, and the specific reverse salt flux (<semantics>Js</semantics>/<semantics>Jw</semantics>) was as low as 0.12 g/L. The degree of internal concentration polarization (ICP) was significantly mitigated. The membrane behaved superior to the commercially available fabric-reinforced membranes. This work provides a simple and low-cost approach in the development TFC-FO membrane and shows great potential in the large-scale production for practical applications.